Characteristics of Nori Moringa Leaves with Suweg (Amorphophallus campanulatus) Starch Addition - Rahmawati Rahmawati; Nur Mu’awwinatun (agriTECH, 2023)
Nori is a thin sheet made from dried Porphyra seaweed, which grows only in subtropical climates, posing challenges to its availability in Indonesia. To address this limitation, diversification of nori with other ingredients such as moringa leaves becomes imperative. Moringa leaves are used due to their green color, high nutritional content, and easy availability. A binder and gel-forming agent containing high amylopectin are also needed to achieve a high-quality and compact nori texture. Suweg is an underutilized gel-forming agent with high amylopectin content. Therefore, this research aimed to characterize moringa leaf nori supplemented with suweg starch (Amorphophallus campanulatus) at concentrations of 0%, 1.25%, 2.5%, 3.75%, and 5%. The results indicated that suweg starch influenced tensile strength, thickness, water content, water activity, ash content, and protein, as well as sensory tests for color, aroma, brittleness, and taste, while crude fiber content was not affected. Based on sensory, physical, and chemical tests the best nori was achieved with the addition of 1.25% suweg starch. The result of characterization of this nori included a tensile strength of 355.90 gf, thickness 0.0145 mm, water content 15.50%, water activity value 0.645, ash content 15.30%, protein content 9.88%, and crude fiber of 2.18%. The sensory evaluation showed that the nori had a green color (3.1), a subtle leafy aroma (3.1), slightly broken (2.9), and a slightly bitter taste (3.2) with preference scores categorized as preferred (3.5), slightly favored (3.3), favored (3.7), and moderately liked by the panelists (score 3.3), respectively. The resulting nori has a thinner thickness and lower tensile strength than commercial products